Peranan Persepsi Bauran Pemasaran terhadap Keputusan Pembelian dan Loyalitas Produk Hatten Wines - DEWI, IDA AYU PUTU CITRA; SURYAWARDANI, I GUSTI AYU OKA; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.3, Juli 2017, 2017)
The Role of Marketing Mix Perception on the Purchasing Decision and the Product Loyalty to the Hatten Wines Hatten Wines is a local wine-based local alcoholic beverage product that is sought after by tourists visiting Bali. The decline in product sales turnover of Hatten Wines since 2008 lies behind this study. The purpose of the study was to identify the variables that determine the marketing mix decisions on the product purchases and loyalty toHatten Wines and their constituent indicators and determine the role of the marketing mix perceptions on the purchasing decisions and loyalty to the products of Hatten Wines. The study was conducted in Sanur, Kuta and Nusa Dua by distributing questionnaires to 100 foreign tourists. The data were analyzed based on the factor analysis with SPSS 19 program. The findings showed that the marketing mix variables that determine the purchasing decision and the loyalty to the products of Hatten Wines consist of four variables: product, price, promotion, place and distribution. The product variables are formed from five indicators: brand, flavor, packaging, aroma, and product variety. Price variables are formed from three indicators, namely affordability, price conformity with benefits, and price competitiveness. Promotional variables formed from four indicators of promotional services, promotional media, promotional quality, and promotional quantity. Place and distribution variables are made up of three indicators: place of sale, product availability, and ease of access. The role of the marketing mix perceptions on the purchasing decisions and the product loyalty to Hatten Wines can be explained by the variance value of 60,946%, the remaining 39,054% is influenced by other variables that are not incorporated into the model. Improved marketing mix quality is needed to improve the competitiveness of the products of Hatten Wines from those of imported products.